Consumer sentiment of the regional youth - I. N. Dementieva (Вестник университета, 2024)
In today’s rapidly developing world, young people play an important role in the segment of active consumers of goods and services. Their behaviour in the consumer market is formed under the influence of subjective moods, ideas, assessments, and expectations. The purpose of this work is to study the state and dynamics of consumer sentiment among young people in the Vologda region using the results of public opinion monitoring and using the index method of processing sociological information. The results of the study showed that the consumer behaviour of young people has a number of specific characteristics: rationality, responsiveness to new products, spontaneity, desire to follow fashion, status. The formation of various consumption models and practices among representatives of the younger generation is largely determined by consumer sentiment. During the measurement period, young people’s assessments were dominated by negative characteristics of their financial situation, opportunities for purchasing goods and services, current economic situation and prospects for its further development. The unfavorable consumer sentiment of the youth significantly deforms its typical features of consumer behaviour, hinders the formation of modern consumer practices and the development of the regional consumer market in accordance with new all-Russian and global trends. Improving the consumer sentiment of young people is directly related to enhancement of the state’s youth and economic policies aimed at improving the socio-economic situation of young members of the Russian society and creating sufficient guarantees for young citizens to exercise their rights and freedoms.